POTENTIAL OF CARRAGEENAN-BASED BIODEGRADABLE FILM WITH TAPIOCA STARCH ADDITION: A REVIEW - Rochima, Emma; Yustiati, Ayi; Anggraeni, Santi Rukminita; Damayanti, Regita (UNIVERSITAS MUHAMMADIYAH PONTIANAK, 2025)
The increasing waste production in Indonesia, particularly plastic waste, poses significant environmental challenges. To address this issue, biodegradable films (biofilms) made from natural polymers like carrageenan and tapioca starch are being explored as eco-friendly alternatives for packaging materials. Carrageenan, a polysaccharide extracted from red algae, has potential as a biofilm due to its stability and gel-forming properties. However, it has poor water resistance and elasticity, which can be improved by adding plasticizers and carbohydrate fillers like tapioca starch. Tapioca starch enhances the flexibility and strength of biofilms, making them suitable for packaging applications. Thickness, tensile strength, elongation, tear resistance, surface morphology, soil degradation, functional group analysis, solubility, water absorption, water vapor transmission rate, color, and transparency are important in characteristics and quality.